2021
DOI: 10.1101/2021.04.19.440349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoconfinement of Microvilli Alters Gene Expression and Boosts T cell Activation

Abstract: T cells sense and respond to their local environment at the nanoscale by forming small actin-rich protrusions, called microvilli, which play critical roles in signaling and antigen recognition, particularly at the interface with the antigen presenting cells. However, the mechanisms by which microvilli contribute to cell signaling and activation is largely unknown. Here, we present a tunable engineered system that promotes microvilli formation and T cell signaling via physical stimuli. We discovered that nanopo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Moreover, TCRs were clearly localized through the microvilli stems and tips, which are enriched with ezrin and F-actin, and were released through long rod-shaped fragments. Furthermore, it is now generally accepted that microvilli play an important role in sensing, particularly at the interface with the APCs ( 12, 30, 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TCRs were clearly localized through the microvilli stems and tips, which are enriched with ezrin and F-actin, and were released through long rod-shaped fragments. Furthermore, it is now generally accepted that microvilli play an important role in sensing, particularly at the interface with the APCs ( 12, 30, 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regulations of T cell activation upon nanoconfinement of microvilli into nanoarchitected pores was demonstrated by Aramesh and co‐workers. [ 108 ] Through forming small actin‐rich protrusions (microvilli), T cells respond to local environments as seen in signaling and antigen recognition. This study revealed that microvilli was favorably formed at nanoporous surfaces, resulting in changes of gene expression of the T cells accompanied with T cell activation.…”
Section: Mechanical Control Of Biosystemsmentioning
confidence: 99%
“…[ 57,58 ] Our recent publication using nanoporous substrates, led to a strongly enhanced T cell activation and proliferation, compared to flat substrates. [ 59 ] Together the signal processes mediated through microvilli represent potential targets for immune therapies as well as to facilitate an enhanced tumor infiltration and killing capacity.…”
Section: Ecm Microarchitecture and Stiffness Influence T Cell Activat...mentioning
confidence: 99%